Predicting subacute hematological toxicity of 177Lu-DOTATATE therapy using healthy organs' uptake on post-treatment quantitative SPECT: A pilot study. Issue 49 (9th December 2022) - Morland, David; Triumbari, Elizabeth Katherine Anna; Hoog, Christopher; Sézin, Ghali; Dejust, Sébastien; Cadiot, Guillaume; Paris, Pierre; Papathanassiou, Dimitri
Abstract : The aim is to investigate the usefulness of 177 Lu-DOTA-0-Tyr3-Octreotate (DOTATATE) healthy organs' (spleen, kidneys, bone marrow) standard uptake value for the prediction of subacute hematological toxicity in patients undergoing 177 Lu-DOTATATE treatment. All patients referred from January 2021 to May 2022 for 177 Lu-DOTATATE treatment were retrospectively screened. For each treatment session, baseline clinical data including age, sex, weight, delay between 177 Lu-DOTATATE treatment and last cold somatostatin analogue intake were collected. Mean standardized uptake value (SUVmean) of healthy organs was measured and analyzed by generalized linear mixed effect models. Outcomes (significant decrease of platelets, hemoglobin levels and neutrophils) were assessed 1 month later, considering their within-subject biological coefficient of variation, published by the European Federation of Clinical Chemistry and Laboratory Medicine. A total of 9 patients (33 treatment sessions) were included. No predictive factors were identified for platelet and neutrophil decrease. Splenic SUVmean was found to be a significant predictor of hemoglobin levels decrease. Using an optimal threshold of ≥6.22, derived sensitivity and specificity to predict hemoglobin decrease were 85.7% [46.4; 99.0] and 76.9% [57.5; 89.2] respectively with an accuracy of 82.4%. Although not significantly predictive of hematological toxicity, bone marrow SUVmean and renal SUVmean were correlated with splenic SUVmean. Quantitative single photon emission computed tomography and healthy organs analysis might help to foresee hematological subacute toxicity in patients undergoing 177 Lu-DOTATATE treatment and improve patient management.